2018
DOI: 10.15666/aeer/1603_36693689
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Organic and Conventional Farming Practices on Microbial Biomass Carbon, Enzyme Activities and Microbial Populations in Different Textured Soils of Haryana State (India)

Abstract: Sheoran et al.: Long term effect of farming practices on microbial biomass carbon, enzyme activities and microbial populations in different textured soils -3669 -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…These are responsible for converting nutrients into forms available to plants. This is confirmed by previous studies on enzyme activity conducted by Furtak and Gajda [63] and Sheoran et al [64]. The CV analysis for the two soil-use systems ranked the enzymes as follows: for CF soils: AlP > AcP > CAT > DEH; and for OF soils: AlP > CAT > AcP > DEH, showing that alkaline phosphatase was the most sensitive to the cultivation treatments used.…”
Section: Discussionsupporting
confidence: 86%
“…These are responsible for converting nutrients into forms available to plants. This is confirmed by previous studies on enzyme activity conducted by Furtak and Gajda [63] and Sheoran et al [64]. The CV analysis for the two soil-use systems ranked the enzymes as follows: for CF soils: AlP > AcP > CAT > DEH; and for OF soils: AlP > CAT > AcP > DEH, showing that alkaline phosphatase was the most sensitive to the cultivation treatments used.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, it should be noted that certain fungi (Bipolaris, Acremonium, Mucor, Fusarium) were found only on organic fruit. Considering the above, along with the observations and results of other authors 22 it can be assumed that the cultivation system (organic or conventional) had a significant impact on fungi. The cultivation system significantly affected the number of yeasts and moulds as well as the taxonomic composition of fungi.…”
Section: Discussionmentioning
confidence: 90%
“…Both types of fruit may pose a threat to the consumer: fruits from conventional crops may have pesticide residues, and fruits from organic farms may contain mycotoxins 12,25 . A well-known thesis was confirmed that the use of pesticides and synthetic fertilizers (strong interference with natural plant growth) changes the plant microbiome 22,23 . The same cultivar of blueberries, cultivated on the same soil, but in a different way, differed in the composition of fungi.…”
Section: Discussionmentioning
confidence: 96%
“…It also indicates that organic soils have higher rate of biological oxidation due to higher microbial activity [16]. The presence of larger quantities of organic substrates enhanced the microbial activity to produce enzymes [39] and also the increase in the release of root exudates by the crops stimulated the microbial growth [40].…”
Section: Soil Biological Propertiesmentioning
confidence: 99%